Phytochemical Profiling of Tampoi (Baccaurea macrocarpa (Miq.) Mull. Arg.) Leaves Using Liquid Chromatography-Tandem Mass Spectrometry - Gaol, Agnes Della Lumban; Sujarwati (Jurnal Biologi Tropis, 2025)
Tampoi leaves (Baccaurea macrocarpa (Miq.) Mull. Arg.) have been reported to contain a diverse array of phytochemicals associated with various biological activities, including antioxidant and antibacterial effects, as well as the enhancement of erythrocyte and hemoglobin levels in anemic mouse models. This study aimed to comprehensively characterize the phytochemical profile of tampoi leaves to establish a foundation for elucidating the mechanisms underlying their biological activities. Extraction was conducted using a solid phase method with methanol as the solvent. Phytochemical profiling was performed using Liquid Chromatography Tandem Mass Spectrometry (LCMS/MS) in positive ionization mode, and data analysis was carried out using MassLynx software. The analysis revealed the presence of 39 phytochemical compounds in the methanolic extract of tampoi leaves. These compounds were classified into 12 major groups: coumarin, amino acid, glycosides, flavonoids, inositol, tannin, terpenoids, jasmonic acids, alkaloids, saponin, phenols, and fatty acids. Among these, terpenoids constituted the most abundant class, comprising nine compounds. Vitexin and linolenic acid exhibited the highest chromatographic peaks, indicating relatively high abundances compared to other constituents in the extract. The phytochemical profile of tampoi leaves offers a valuable basis for understanding the interactions between bioactive compounds and biological targets through in silico approaches, thereby supporting the development of phytopharmaceutical candidates.